Armand Tagoona and the Arctic Christian Fellowship : the first Inuit church in Canada - Laugrand, Frédéric.; Laneuville, Pascale (Cambridge University Press, 2020)
Armand Tagoona (1926–1991) was born in Naujaat (Repulse Bay, Northwest Territories) in 1926, from an Inuk mother and a German father. Born as a Roman Catholic, he converted to Anglicanism. In 1969, he founded a new independent religious group affiliated to the Anglican Church in Qamani’tuaq (Baker Lake, Northwest Territories): the Arctic Christian Fellowship (ACF). In this paper, we examine his life briefly as well as this very first “Inuit church” he created. We argue that Tagoona played the role of a mediator encompassing various religious traditions and various cultures at a time when solid boundaries separated all these institutions. In bridging them, Tagoona’s church turned to be very innovative and aimed at more religious autonomy, while being fundamentally guided by the words of God. Tagoona’s church carries conversionist, reformist and utopian aspects at the same time.